Heart in hardware a thematic construction of DIY electronics as a studio practice in the Philippines - Rubis, Kyle; Yraola, Dayang Magdalena Nirvana T. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2024)
This research explores the themes and practices of DIY electronics in the creation of electronic art, encompassing objects, performances, and programs that utilize electronics in their production. Artists in this field often adopt DIY approach, integrating diverse areas of knowledge. The study addresses three primary questions: how artists incorporate DIY electronics into their practice, how the DIY approach manifests in the creation and objects of electronic art, and how the DIY ethos influences the discourse surrounding technology and art.

The research examines DIY electronic art at both individual and community levels, positioning it as a transversal practice that transcends traditional boundaries of knowledge and practice. This transversality allows DIY electronics to de-territorialize these structures of knowledge and foster new forms of material relationships and practices through adhocism (improvised solutions), un-blackboxing (demystifying technology), and community collaboration.

Five key themes define DIY electronic art. First, frugality emphasizes cost-effective, improvised approaches to materials and processes. Second, exploration highlights the experimental and investigatory nature of the practice. Third disobedience challenges conventional norms and bodies of knowledge. Fourth, negotiation involves balancing artistic intent with practical form. Finally, community promotes the sharing, exchange, and expansion of knowledge and skills among practitioners.

By articulating DIY electronic art as both a theoretical framework and a practical approach, this study demonstrates its impact on individual artists and the broader community, showcasing its potential to redefine the intersection of technology and art.
Thesis (Bachelor of Fine Arts in Art History)--University of the Philippines Diliman
Bibliography: leaves 76-78
Keywords: Do-it-yourself electronics; Video art; Transversality; Art and technology